2018
DOI: 10.3389/fmicb.2018.01030
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of Milkisin, a Novel Lipopeptide With Antimicrobial Properties Produced By Pseudomonas sp. UCMA 17988 Isolated From Bovine Raw Milk

Abstract: Biosurfactants such as lipopeptides are amphiphilic compounds produced by microorganisms such as bacteria of the genera of Pseudomonas and Bacillus. Some of these molecules proved to have interesting antimicrobial, antiviral, insecticide, and/or tensioactive properties that are potentially useful for the agricultural, chemical, food, and pharmaceutical industries. Raw milk provides a physicochemical environment that is favorable to the multiplication of a broad spectrum of microorganisms. Among them, psychrotr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 48 publications
0
10
0
1
Order By: Relevance
“…Ultimately, Schlusselhuber et al (2018) reported Pseudomonas strain UCMA 17988, isolated from raw cow milk, for its ability to produce lipopeptide BS, although Pseudomonas spp. are famous for rhamnolipid production (Pornsunthorntawee et al, 2010).…”
Section: Lipopeptide Biosurfactantsmentioning
confidence: 99%
“…Ultimately, Schlusselhuber et al (2018) reported Pseudomonas strain UCMA 17988, isolated from raw cow milk, for its ability to produce lipopeptide BS, although Pseudomonas spp. are famous for rhamnolipid production (Pornsunthorntawee et al, 2010).…”
Section: Lipopeptide Biosurfactantsmentioning
confidence: 99%
“…Similarly, another study reported Pseudomonas strain UCMA 17988, isolated from raw cow milk, for its ability to produce a lipopeptide biosurfactant. The antimicrobial activity of the major isolated isoforms of the biosurfactant was observed against S. aureus with a MIC of 0.5 µg/mL against L. monocytogenes and Salmonella enterica with a MIC of 1 µg/mL [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, other Gram-negative and Gram-positive bacteria tested were insensitive to those compounds used at a similar concentration. In many studies, when available, MIC values of lipopeptides against bacteria ranged from less than 10 μ g/ml (massetolide A and viscosin against M. tuberculosis ) to around 1 mg/L (milkisin against S. enterica ) [ 37 , 51 ]. Thus, MIC determined in this study were in a similar concentration range.…”
Section: Discussionmentioning
confidence: 99%